PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE DAN TAX PLANING TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MODERASI - Sri Lestari Yuli Prastyatini; MARIA CENDRIANA RIA (Jurnal Riset Perpajakan: Amnesty, 2021)
This study aims to examine whether CSR disclosure and tax planning can affect the value of companies with earnings management as a moderating variable This study took samples from the Indonesia Stock Exchange (IDX) from 2016-2019 in property and real estate companies using a purposive sampling technique. Data collection is done by accessing www.idx.co.id then processed using SPSS. The results show that the corporate social responsibility disclosure variable has a positive and significant effect on firm value in Property and Real Estate companies on the Indonesia Stock Exchange in 2016-2019, the tax planning variable has no effect on firm value in Property and Real Estate companies on the Stock Exchange. Indonesia in 2016-2019, Earnings management moderated the influence of corporate social responsibility disclosure on the company's firm value. In this study, earnings management strengthens the relationship between CSR disclosure and firm value. Earnings management moderates the effect of tax planning on firm firm value. In this study, earnings management weakens the relationship between tax planning and firm value.